Dinamika Filologi Di Era Digital: Jembatan Kemudahan Atau Pengikisan Otentisitas? - Agus Srimudin; Nyimas Umi Kalsum; Oman Fathurahman; Lukman; Novasriady; M. Rasya Alfarizi Srimudin (CV. Era Digital Nusantara, 2026)
The development of digital technology has permeated all areas of classical scholarship, including philology. The aim of this study is to examine the dynamics of philological development in the digital age. It seeks to assess the extent to which digitalisation acts as a tool that can facilitate research or, conversely, erode the distinctive characteristics of classical philology. The approach in this study is a qualitative descriptive approach, using a literature review method that examines the implementation of traditional philology and digital philology. The findings of this study indicate that the digital era has inevitably permeated every sphere, offering convenience to society whilst simultaneously bringing about certain impacts: digitalisation democratises access to manuscripts, facilitates efficient text preservation, and ensures ease of access; yet, on the other hand, this digital space poses a significant risk of eroding the authenticity of manuscripts, reducing sensory-based physical analysis (codicology), and may even lead to the decline of manual palaeographic skills and the next generation of philologists. It can be concluded that digital technology for the generation of digital philologists must be positioned as an instrument of acceleration, The wise integration of classical and digital methods is key to maintaining the relevance of philology without losing its academic identity in the future.